Calculus Flanders / Florida Atlantic University - Flanders Harley (W. H. Freeman And Company, 1985)
Preface, Functions and Graphs, The Derivative, Applications of Differentiation, Special Functions, Integration, Techniques of Integration, Applications of Integration, Analytic Geometry, Numerical Calculus, Sequences and Series, Power Series, Space Geometry, Vector Functions, Functions of Several Variables, Surfaces and Optimization, Higher Partial Derivatives, The Double Integral, Multiple Integrals, Differential Equations, Answers to Odd-Numbered Exercises, Index.